Analyzing the causes of method-to-method variability among Rubisco kinetic traits: from the first to the current measurements. (30th July 2021) - Iñiguez, Concepción; Niinemets, Ülo; Mark, Kristiina; Galmés, Jeroni
Abstract : This study highlights the methodological causes responsible for the intraspecific variability among Rubisco kinetic traits and provides a normalized kinetic dataset for model species to be used by the scientific community. Abstract: Due to the importance of Rubisco in the biosphere, its kinetic parameters have been measured by different methodologies in a large number of studies over the last 60 years. These parameters are essential to characterize the natural diversity in the catalytic properties of the enzyme and they are also required for photosynthesis and cross-scale crop modeling. The present compilation of Rubisco kinetic parameters in model species revealed a wide intraspecific laboratory-to-laboratory variability, which was partially solved by making corrections to account for differences in the assay buffer composition and in the acidity constant of dissolved CO2, as well as for differences in the CO2 and O2 solubilities. Part of the intraspecific variability was also related to the different analytical methodologies used. For instance, significant differences were found between the two main methods for the determination of the specificity factor ( S c/o ), and also between Rubisco quantification methods, Rubisco purification versus crude extracts, and single-point versus CO2 curve measurements for the carboxylation turnover rate ( k cat c ) determination. Causes of the intraspecific laboratory-to-laboratory variability for Rubisco catalytic traits are discussed. This study provides a normalized kinetic dataset for model species to be used by the scientific community. Corrections and recommendations are also provided to reduce measurement variability, allowing the comparison of kinetic data obtained in different laboratories using different assay conditions.